(3eMGSHI GdJcGdja dCZQGV GdJNWjW h GdQbGHI h GJNGP GdbQGQGJs - (3GdCejQI GHQGgje(B, (3YKeGfs; (3CMeO eMeO cGed(B, (3SGdes ((3GdGScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2006)
1) (3VHW h QbGHI GdCOGA HGdJWQb Gdi GSJNOGe GdeYGjjQ cCOGI QbGHjI , JMdjd EfMQGaGJ GdGjQGOGJ h GdCQHGM , VHW h QbGHI JcdaI GdehGO GdeHGTQI h GdCLhQ GdeHGTQI , VHW h QbGHI GdJcGdja GdUfGYjI ZjQ GdeHGTQI , GSJNOGe HYV GdCSGdjH GdGMUGFjI aj GdQbGHI Ydi GdJcGdja (B2) (3GSJNOGeGJ HjGfGJ GdJcGdja aj GJNGP GdbQGQGJ (B: (3JMdjd YdGbI GdJcdaI (B/ (3GdMLe (B/ (3GdQHM ,JMdjd GdJYGOd aj Xd MGdGJ GdNWQ , eOGNd bjGS JcdaI GdGfJGL(B.s
Keywords: (3GJNGP GdbQGQGJs; (3GdQbGHIs; (3eMGSHI GdJcGdjas